Cultivating inclusion: measuring safety in Indonesia early childhood education environments for every child - Pratiwi, Hardiyanti; Riwanda, Agus; Islamy, M. Irfan (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Safety holds paramount importance in inclusive school environments that accommodate all students. The UNICEF report emphasizes that, regrettably, both peers and teachers may engage in physical abuse against children in early childhood education (ECE). Objective. This paper aims to assess early childhood education teachers' perspectives on school safety, their strategies to ensure a safe environment, and the supporting rules for school environmental safety. Method. This research employed a quantitative descriptive approach, gathering numerical data through a survey questionnaire. The study included 52 ECE teachers who had undergone anti-violence education training in Banjarmasin and Banjarbaru, two inclusive cities in South Kalimantan, Indonesia. Results. Findings reveal that teachers reported instances of physical aggression, cyberbullying, verbal insults, and sexual harassment as infrequent occurrences. However, addressing social manipulation and physical aggression through corrective measures is recognized as necessary. Teachers implemented diverse strategies to maintain a safe and respectful classroom atmosphere, including reinforcing norms, promoting civility, teaching non-violent conflict resolution, and acknowledging students who intervened to protect victims. Importantly, teachers affirmed their commitment to transparency by refusing to conceal unethical behaviors by staff or students, thereby strengthening school safety protocols. Nevertheless, the evaluation of school environmental safety activities and regulations identified significant opportunities for improvement. Conclusion. The majority of ECE institutions lack clear protocols for conflict resolution, diversity promotion, bullying prevention, parental involvement, teacher training, and safety assessment. Addressing these shortcomings is crucial to establishing a more secure and inclusive learning environment that meets the needs of all children.
Keywords: safety environment, teachers' strategies; school safety procedures; inclusive early childhood education